Desempenho motor em habilidades básicas e força muscular dinâmica de crianças com diferentes níveis de coordenação motora conforme o MABC-2 - Guilherme Eugênio van Keulen (2017)
Different levels of motor coordination (MC) have been portrayed based on the performance level of motor skills, which involve fine and gross motor coordination, balance, strength and accuracy. Taking into account how these variables influence the level of MC, This study aimed at analyzing the performance level of motor skills and the maximum dynamic muscular strength (MDMS) of children with different levels of MC. A total of 150 children (8.68 ± 0.88 years) participated in two different experiments. The first experiment characterized the level of MC, the level of performance level of motor skills and verified the level of performance level of motor skills according to the level of MC. The second, experiment analyzed the MDMS of the anterior and posterior muscular chains; Examined the MDMS of the muscular chains of the children with low MC and with typical MC; and compared the MDMS of the anterior muscular chain with that of the posterior muscular chain of children with low MC and with typical MC. MC was measured by using the MABC-2 test while performance level of motor skills levels were determined by using the TGMD-2 test. To assess the MDMS, the maximal 1 repetition test (1 RM) was used. To verify the level of performance level of motor skills according to the level of MC, two groups were created: low MC (LMCG) and typical MC (TMCG). Whit respect to MC, 3.3% of the children presented motor impairment and, 86.7% typical MC. The performance level of motor skills analysis showed that 76% of the children had lower than average performance level of motor skills, and of these, 28.7% showed below average performance level of motor skills; 32% with poor performance level of motor skills and, 15.3% with very poor performance level of motor skills. When the level of performance level of motor skills was compared with the level of MC, the LMCG were worst performance level of motor skills than TMCG. The Chi-square analysis detected a significant association between LMCG and poor performance level of motor skills; and between TMCG and the performance level of motor skills below average. TMCG presented values of strength, both of the anterior and posterior chains, significantly higher than the LMCG. In the comparison of the strength between the muscle chains, both LMCG, and TMCG, no significant differences were found. It was concluded, therefore, that the children presented a typical motor coordination according to the MABC-2 and the motor performance was below the average expected for the age. The data also suggest the influence of motor coordination on the performance of maximum dynamic muscle power and motor performance, since children with motor coordination difficulties presented worse performance in both variables. In the future, other studies could include additional groups to conduct an experimental design with control groups. Perhaps it is also interesting to analyze other age groups and the correlation of strength with other physical abilities.